2015
DOI: 10.1097/qad.0000000000000731
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the impact of within-host evolution and transmission dynamics on the tempo of HIV-1 evolution

Abstract: Background Although evidence exists for a selective component at transmission, it is clear that HIV-1 transmission is also to a large extent driven by drift. The variation in inoculum size among different risk groups therefore implies that the adaptation rate of HIV may vary between epidemics with different risk group compositions. Furthermore, factors that govern the rate of within-host evolution may also vary by risk group and therefore contribute to evolutionary differences at the epidemic level. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 65 publications
0
12
2
Order By: Relevance
“…Recent studies have investigated transmission dynamics and within-host virus evolution to explain risk group-associated ( i . e ., MSM, HET, or IDU) differences in HIV-1 evolution at the population level [ 18 , 23 , 111 ], as this may help to inform treatment and prevention strategies within certain demographics. For instance, Vrancken et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have investigated transmission dynamics and within-host virus evolution to explain risk group-associated ( i . e ., MSM, HET, or IDU) differences in HIV-1 evolution at the population level [ 18 , 23 , 111 ], as this may help to inform treatment and prevention strategies within certain demographics. For instance, Vrancken et al .…”
Section: Discussionmentioning
confidence: 99%
“…Vrancken et al . reported that evolutionary rates were lowest in heterosexual (HET) compared to MSM and intravenous drug users (IDU) [ 23 ], and the authors suggested that gender ratios within a given risk group may explain the associated evolutionary rate differences. Specifically, the incidence of multi-variant transmission is reported to be 2-fold higher in MSM [ 24 ] than in HET risk groups [ 7 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…This rate tended to be higher for the lineages formed largely by MSMs and IVDUs, which suggests greater transmission efficiency and faster subtype B evolution in the groups at risk of HIV-1 infection [41]. …”
Section: Discussionmentioning
confidence: 99%
“…To further assess the presence of viral evolution, we applied a Bayesian approach to our heterochronous data set. While these techniques have been used to estimate the evolutionary rate of HIV RNA populations (43,44), little is known about the efficacy of these methods to…”
Section: Figmentioning
confidence: 99%